2019
DOI: 10.21203/rs.2.16746/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in children’s oral-health-related quality of life following dental treatment under general anesthesia in the United Arab Emirates

Abstract: Background Early Childhood Caries (ECC) is the most common childhood disease in preschool children which often require dental treatment under Dental General Anaesthesia (DGA). Aim: To assess the effect of DGA on United Arab Emirates (UAE) children and their families’ Oral Health Related Quality of Life (OHRQoL). Design: A cross sectional study, using a DGA pre-and post-survey to evaluate changes in OHRQoL. A total of 173 parents completed Early Childhood Oral Health Impact Scale (ECOHIS) before and after their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(55 reference statements)
1
0
0
Order By: Relevance
“…Moreover, in this study, S-ECC was found to be the most common cause of DGA (85%). These results seem to be consistent with other studies, which found that most of their DGAs were also caused by S-ECC [ 14 16 ]. These findings are rather disappointing and suggested that ECC, a preventable disease, remains a burden upon children, families, and the wider society that needs to be resolved.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in this study, S-ECC was found to be the most common cause of DGA (85%). These results seem to be consistent with other studies, which found that most of their DGAs were also caused by S-ECC [ 14 16 ]. These findings are rather disappointing and suggested that ECC, a preventable disease, remains a burden upon children, families, and the wider society that needs to be resolved.…”
Section: Discussionsupporting
confidence: 93%
“…Research on addressing fear and anxiety in treating anxious children has explored the use of tranquilizers, narcotics, behavior control techniques, or a combination thereof (3)(4)(5). However, behavior control techniques come with limitations, notably their potential ineffectiveness at higher levels of anxiety (6). Combining pharmaceutical management with behavior control methods in pediatric dentistry enhances the success rate and quality of treatments.…”
Section: Introductionmentioning
confidence: 99%